THE ROLE OF ECONOMIC AND SOCIO-POLITICAL VALUES IN THE SPIRITUAL EXISTENCE OF MAN IN THE CONTEXT OF RENEWED UZBEKISTAN - Ismatullayeva Feruza (Web of Journals Publishing, 2025)
This article explores the role and significance of economic and socio-political values in shaping the spiritual identity of individuals within the context of the ongoing renewal in Uzbekistan. As the country undergoes dynamic reforms aimed at building a modern and just society, the formation of a morally grounded personality has become one of the key priorities of national development. The paper analyzes how economic progress and political stability intersect with spiritual education, national values, and ethical behavior, ultimately contributing to the cultivation of socially responsible and ideologically conscious citizens. The study also emphasizes the necessity of integrating traditional values with contemporary socio-political norms to ensure a balanced and holistic development of the individual in the New Uzbekistan.
Keywords: Political culture, political values, value system, transmission, manipulative influence, conformist adaptation, identification, hierarchy of needs, postmaterialism, stability and changes in the value system.